Work Function Modulation with Self-assembled Monolayers: Effect of Dipole Moment on Packing Density - Nurfitria, Nia; Tao, Yu-Tai; Huang, Ding-Chi (IPTEK Journal of Proceedings Series, 2015)
A series of benzylmercaptans carrying different para-substituents were used to form self-assembled monolayers on gold in order to modulate the work funtion of the metal electrode. Ellipsometry, Reflection Absorption Infrared Spectroscopy (RAIRS), and cyclic voltametry were used to chracterized the structure of the monolayer. The results show that as the dipole moment increases in the molecule, the surface coverage decreases. This can be the reason that a more polar molecule does not necessarily generate work function change proportionally.